Clinical valuation of ST changes in a group of patients with ventricular arrhythmias: The inSighT Study. Issue 3 (15th February 2022) - Wranicz, Jerzy Krzysztof; Kałowski, Michał; Bastian, Dirk; Jaswal, Aparna; Kolb, Christof; Zitron, Edgar; Cygankiewicz, Iwona; Kaczmarek, Krzysztof
Abstract: Background: The inSighT study was designed to determine the prevalence of ischemic changes as recorded by implantable cardioverter–defibrillator (ICD) ST deviations in intracardiac electrocardiograms (EGM) over the 24 h preceding malignant ventricular arrhythmias (VT/VF). Methods: The study enrolled patients with known coronary artery disease (CAD) or high risk of future development of CAD implanted with an ICD equipped with an ST monitoring feature (Ellipse™/Fortify Assura™, St. Jude Medical). Device session records were collected at each in‐clinic follow‐up. EGM ST levels of the beats over the 15 minutes prior to VT/VF events were compared using a t test with those from a baseline period of 23–24 h prior to the VT/VF event. All events with p < .05 were visually inspected to confirm they were evaluable; additional criteria for exclusion from further analysis included inappropriate therapy, aberrant conduction, and occurrence of VT/VF within 24h prior to the current event. Results: The study enrolled 481 ICD patients (64 ± 11 years, 83% male) in 14 countries and followed them for 15±5 months. A total of 165 confirmed VT/VF episodes were observed, of which 71 events (in 56 patients, 34% of all patients with VT/VF) were preceded by significant ( p < .05) ST‐segment changes unrelated to known non‐ischemic causes. None of the analyzed demographic and clinical factors proved to be associated with greater odds of presenting with ST‐segment changes prior to VT/VF episode. Conclusion: In this exploratory study, characteristic ST‐segment changes, likely representative of ischemic events, were observed in 34% of all patients with VT/VF episodes. Abstract : Analysis of VT/VF events and preceding ST‐segment changes.